Uplift force and momenta on a slab subjected to hydraulic jump - Mauricio Gonzalez Betancourt (Dyna, 2016)
As part of the search for safe and economic design criterion to line slabs of stilling basins, the present study is one of the first to calculate the center of pressure, uplift forces, and momenta from a spatiotemporal analysis of the pressures measured above and below instrumented slabs in a physical model. Controlled release of the waterstops, and variation in the dimensions of expansion joints and in the gap between foundation and the lining slab were carried out in order to consider their effects on the magnitudes of uplift forces and momenta. An offset of the center of pressure from the slab’s center of gravity was identified. The objective of this work was to consider the failure mechanism induced by momentum in the slab’s design. Design criterion to make the lining slab’s thickness to length between 6 and 12 times the incident flow depth, is proposed, and this is compared to other design criteria.